PERAN MAHKAMAH KONSTITUSI DALAM MENJAMIN HAK-HAK KONSTITUSIONALWARGA NEGARA (Faculty of Social Science, Universitas Negeri Semarang, 2013)
The Constitutional Court as the judicial authority is responsible for maintaining the constitution directly and participates in strengthening the rights of human rights. This is drawn directly from the nature of the understanding that the constitution itself as a political document that protects the rights of human rights of every citizen and people who live in the country. The constitutional functions are the first, limiting the powers contained in the constitutional scheme of a nation, and second, to formulate protection constitutional rights of the citizens and the rights of human as a whole. That is why the role of the Constitutional Court directly correlated with the significance of the role of enforcement agencies of human rights in terms of “norms control”. Embodiment of constitutional and judicial review is examining through compliance with the norms of the constitution messages that cannot be separated from the universality of normative messages of human rights.